PENGARUH PENERAPAN MODEL MOODY TERHADAP KEMAMPUAN SISWA KELAS IV SD DALAM MEMAHAMI ISI CERITA - Dadang Cunandar (Jurnal Lensa Pendas, 2019)
This study aims to determine the effect of the application of the Moody Model on the ability to understand the contents of the story in fourth grade students of SDN 2 Karoya. This research is an experimental research. The study population was all fourth grade students of SD Negeri 2 Karoya, Cipicung Subdistrict, Kuningan Regency, totaling 24 students. The sampling technique in this study was total sampling. Data collection techniques in this study were tests and documentation. Data analysis techniques through normality test, homogeneity test, and hypothesis test (t-test). The results of the study, (1) the ability of fourth grade students of State 2 Karoya in tracing elements of folklore structure before using the Moody model, is low with an average value of 57.33. (2) the ability of fourth grade students of Country 2 Karoya to trace the structural elements of folklore after using the Moody model, increasing with an average value of 81.5. (3) there is the effect of applying the Moody model on students' ability to trace elements of folklore